Effectiveness of nicotine withdrawal symptom management program for industrial workers in contemplation and preparation stages of tobacco quitting process - Kamonkriangkrai, Sansanee; Keawpan, Wonpen; Kalampakorn, Surintorn; Sillabutra, Jutatip (Thai Journal of Nursing, 2022)
The objective of this quasi–experimental study was to examine the effectiveness of the nicotine withdrawal symptom management program for industrial workers at contemplation and preparation stages of tobacco quitting process. Sixty participants were purposively selected from male workers at a factory in Bangkok Metropolitan. Simple random technique was employed to separate equally into the experimental group and the comparison group. The self-administered questionnaire was used to assess nicotine withdrawal symptoms, tobacco cravings and perceived capability to quit smoking. The program consists of 3-weeks activities and 1-week follow-up. Mann-Whitney U Test was employed for data analysis. Results revealed that after the implementation of the nicotine withdrawal symptom management program, industrial workers at contemplation and preparation stages of tobacco quitting process in the experimental group had nicotine withdrawal symptoms, tobacco craving, and perceived capability to quit smoking better than the comparison group at p < .01 after experiment and at follow-up stages.